Synthesis of silicon carbide nanomaterials by microwave heating: Effect of types of carbon nanotubes - Tony, V.C.S.; Voon, C.H.; Lim, B.Y.; Al-Douri, Yarub; Gopinath, S.C.B.; Arshad, M.K. Md; Ten, S.T.; Parmin, N.A.; Ruslinda, A.R. (Elsevier, 2019)
One-dimensional silicon carbide nanomaterial (SiCNM) is the leading potential material for high temperature, high power and harsh environment components and devices. This is due to the outstanding properties of the one-dimensional SiCNMs such as high mechanical properties, high hardness, good chemical inertness and excellent electronic properties. In this paper, we reported the successful synthesis of one-dimensional SiCNMs from blend of SiO2 particles with two types of CNTs, namely MWCNTs and SWCNTs by using microwave heating and the effect of types of CNTs on the synthesis of one-dimensional SiCNMs. The result of x-ray diffraction, field emission scanning electron microscopy, high resolution transmission electron microscopy, energy dispersive x-ray spectroscopy, photoluminescence spectroscopy, Fourier transform infrared spectroscopy and thermo-gravimetric analysis revealed that high purity of β-SiC nanotube was obtained from blend of SiO2 particles and MWCNTs while solid SiC nanowire was synthesized from blend of SiO2 particles and SWCNTs and associated with the presence of residual of unreacted SiO2 particles. This clearly shows that types of one dimensional SiCNMs (hollow or solid) can be controlled by using different types of CNTs and thus this study proposed a high efficiency microwave heating method for the synthesis of one-dimensional SiCNMs with controllable morphology. © 2019 Elsevier Masson SAS